Penerapan Model Pembelajaran Project Based Learning (PjBL) untuk Meningkatkan Hasil Belajar Siswa Kelas 1 SD Negeri 33 Mataram - Hendri, Muhammad; Witono, A.Hari; Lestari, Sri (Lembaga Yasin AlSys, 2023)
This research aims to describe the steps for implementing the project based learning (PjBL) learning model in improving learning outcomes, knowing the increase in learning outcomes. The type of this research is classroom action research (PTK) which is carried out in two cycles. This research was carried out at SD Negeri 33 Mataram with the research subjects being grade 1 students at SD Negeri 33 Mataram with a total of 28 children as subjects. Data collection techniques use test techniques. The data analysis used is quantitative descriptive. The research results show that there is an increase in learning outcomes through the application of the Project Based Learning learning model for grade 1 students at SD Negeri 33 Mataram. This is evidenced by the increase in student learning outcomes with the average student learning outcomes in the initial condition being 55 with 10 students (36%) experiencing an increase in cycle 1 with an average student score of 67 with 17 students (60%) and in cycle 2 The average student score is 82 with the number of students completing as many as 25 or (89%) students completing.